Investigating sacred natural sites and protected areas for forest area changes in Italy. Issue 8 (16th June 2022) - Zannini, Piero; Frascaroli, Fabrizio; Nascimbene, Juri; Halley, John Maxwell; Stara, Kalliopi; Cervellini, Marco; Di Musciano, Michele; De Vigili, Filippo; Rocchini, Duccio; Piovesan, Gianluca; Alessi, Nicola; Chiarucci, Alessandro
Abstract: Forests will be critical to mitigate the effects of climate and global changes. Therefore, knowledge on the drivers of forest area changes are important. Although the drivers of deforestation are well known, drivers of afforestation are almost unexplored. Moreover, protected areas (PAs) effectively decrease deforestation, but other types of area‐based conservation measures exist. Among these, sacred natural sites (SNS) deliver positive conservation outcomes while making up an extensive "shadow network" of conservation. However, little is known on the capacity of SNS to regulate land‐use changes. Here, we explored the role of SNS and PAs as drivers of forest loss and forest gain in Italy between 1936 and 2018. We performed a descriptive analysis and modeled forest gain and forest loss by means of spatial binomial generalized linear models with residual autocovariates. The main drivers of forest area changes were geographical position and elevation, nonetheless SNS and PAs significantly decreased forest loss and increased forest gain. Although the negative relationship between SNS and forest loss is a desirable outcome, the positive relationship with forest gain is concerning because it could point to abandonment of cultural landscapes with consequent loss of open habitats. We suggest a legal recognition of SNS and an active ecological monitoring and planning to help maintain their positive role in biodiversity conservation. As a novel conservation planning approach, SNS can be used as stepping stones between PAs increasing connectivity and also to conserve small habitat patches threatened by human activities.